Explaining the salience of anti-elitism and reducing political corruption for political parties in Europe with the 2014 Chapel Hill Expert Survey data. (January 2017) - Polk, Jonathan; Rovny, Jan; Bakker, Ryan; Edwards, Erica; Hooghe, Liesbet; Jolly, Seth; Koedam, Jelle; Kostelka, Filip; Marks, Gary; Schumacher, Gijs; Steenbergen, Marco; Vachudova, Milada; et al.
This article addresses the variation of anti-corruption and anti-elite salience in party positioning across Europe. It demonstrates that while anti-corruption salience is primarily related to the (regional) context in which a party operates, anti-elite salience is primarily a function of party ideology. Extreme left and extreme conservative (TAN) parties are significantly more likely to emphasize anti-elite views. Through its use of the new 2014 Chapel Hill Expert Survey wave, this article also introduces the dataset.